(untitled) (Journal of the College of Basic Education, 2022)
This research (transformation in the design systems of industrial products in the light of digital technology) deals with the impact of digital technologies on product design systems and their effectiveness in raising the efficiency and work system of the industrial product and the design process. As the importance of this topic comes as a result of the technological development in the field of modern technologies with high capabilities, and the research problem was identified by asking whether the possibility of digital technologies is the basis on which the design (formally and functionally) is built in the future?